Brand Endorsers with Role Model Function - Jessica Kühn; Claudia Riesmeyer (MedienPädagogik, 2021)
Social media influencers (SMIs) are taking on new roles in the communication environment of their followers as persuasive agents, opinion leaders, brand endorsers, and role models. Taking a look from the perspective of SMIs as agents in the persuasion attempt and their advertising literacy, our study has three aims. First, we provide insight into SMIs‘ self-perception as opinion-leading brand endorsers. Second, we discuss the extent to which SMIs use this awareness of and knowledge about their role model function for their particular young followers. Finally, we show how SMIs actively construct their media persona and how their relationship with their followers is based around this identity. The results from 15 semi-structured, guideline-based interviews conducted in 2019 with German SMIs working in different subject areas (e.g., fitness, fashion, travel, and family) show that SMIs are advertising literate. SMIs are aware of their multiple roles (understanding of one‘s roles: conceptional dimension), and reflect about their media persona‘s role model function (role interpretation: attitudinal dimension). Therefore, the majority of SMIs create their content and their media persona, as well as actively construct their relationship to their followers, based on their knowledge and awareness (role construction: performance dimension).